An Evaluation into Strategies for Translating Vietnamese Culture-Specific Expressions in the Novel - Nguyễn Lê Bảo Ngọc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study primarily seeks to scrutinize the Vietnamese -English translation of culture-specific expressions in the novel “Buoc Duong Cung” by Nguyen Cong Hoan. The thesis also explores foreign readers’ perception of translated culture-specific expressions to provide effective solutions for rendering literal masterpieces translated into English more accessible to international readers.